High immersion/escapism motivation makes gaming disorder risk less dependent of playtime among highly engaged male gamers - Kiszka, Patrycja; Strojny, Agnieszka; Strojny, Paweł (Frontiers in Psychiatry, 2024)
In the realm of gaming-related concerns, the relationship between gaming time (GT) and gaming disorder (GD) remains an intriguing and complex subject. Although increased GT is not a reliable predictor of GD risk, the circumstances under which this relationship strengthens or weakens remain relatively unknown. This study explores the roles of immersion/escapism motive (IEM) and GT in the context of GD among highly engaged gamers (N = 294), each dedicating a minimum of 20 hours weekly to gaming. The findings confirm that IEM significantly moderates the relationship between GT and GD in the male sample. Specifically, low and moderate levels of IEM result in a stronger relationship between GT and GD. In the case of women, the effect was not significant. These findings suggest the importance of comprehensive assessments of gaming motivations when addressing gaming-related issues, particularly in GD research. Moreover, they emphasize the value of adopting a complex approach to comprehending the development of problematic gaming behaviors.